Granulomatous osteomyelitis: A review of 13 cases in Port Harcourt, Nigeria - D Seleye-Fubara; E N Etebu; E Bob-Yellowe (Sahel Medical Journal, 2011)
Background: Osteomyelitis is usually caused by many infectious agents but granulomatous osteomyelitis is rare in this setting requiring adequate research into the pattern of the few diagnosed cases. Aim: To study the frequency and pattern of granulomatous osteomyelitis. Design and Setting: A retrospective study in Port Harcourt, Nigeria (from 1 st January 1990 to 31 st December 2004). Method: The tissues were fixed in 10% formalsaline and decalcified with concentrated Nitric or sulfuric acid, and processed and embedded in paraffin wax. The tissues were then sectioned, mounted on glass slide and stained with hematoxylin and eosin (H & E) stains. In some cases special stains (Ziehl-Neelsen and Grocotte′s) were used to demonstrate the acid fast bacilli (AFB) and the fungal elements respectively. Results: There were 13 specimens of which 8 (61.5%) were from males and 5(38.5%) in females giving a sex ratio of 1.6:1. Eight (61.5%) cases occurred in patients under the age of 30 years. The highest frequency of four (30.8%) occurred in patients aged 10 years and below. The youngest was a 3-year-old male while the oldest was a 62-year-old male. Tuberculous (Tb) osteomyelitis accounted for twelve (92.3%) of the cases while histoplasmosis accounted for one (7.1%). One of our patients was HIV positive. The common sites of predilection were the hip joint n-4 (30.8%) and the vertebral column n = 3 (23.1%). Conclusion: Granulomatous osteomyelitis is very uncommon in this environment. Though many organisms maybe associated, only TB and histoplasmosis were seen in this study.